These Shreds, Guardians of Human Memory: Papyrus and Culture in Late Antiquity : Inaugural Lecture delivered on Thursday 7 January 2016 - Jean-Luc Fournet (Collège de France, 2018)
Papyrology, which burgeoned in the nineteenth century after the discovery of thousands of papyri in Egypt, consists in the study of Greek and Latin texts written on a transportable medium (papyrus, clay potsherds, wooden tablets or parchment). While inscriptions and literary sources can render a normative, idealized and sometimes deformed image of individuals, papyri - no matter how fragmented they may be - take us into their daily lives, thus making possible the archaeology of cultural practices. Attempting to decipher "these shreds, guardians of the human memory" - to paraphrase Leonardo de Vinci - is the challenge of the papyrologist, who ceaselessly renews our knowledge of the past.